2018
DOI: 10.1016/j.plaphy.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Eucalypt plants are physiologically and metabolically affected by infection with Ceratocystis fimbriata

Abstract: Ceratocystis wilt, caused by Ceratocystis fimbriata, is currently one of the most important disease in eucalypt plantations. Plants infected by C. fimbriata have lower volumetric growth, lower pulp yields and reduced timber values. The physiological bases of infection induced by this pathogen in eucalypt plant are not known. Therefore, this study aims to assess the physiological and metabolic changes in eucalypt clones that are resistant and susceptible to C. fimbriata. Once, we evaluated in detail their leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 55 publications
0
17
0
3
Order By: Relevance
“…In pathogen-associated mortality, drought stress may change the demographics of pathogens 9 ; pathogens subsequently drive forest mortality independently or in conjunction with drought-induced changes in the host’s physiological condition 11,12 . Pathogen infections also significantly alter physiological performance, such as inhibiting stomatal opening and the photosynthetic rate, thus triggering physiological changes similar to those triggered by drought stress 1315 . This, combined with the increased demand for energy and carbon for disease resistance, depletes the carbon reserve in the sink tissues 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In pathogen-associated mortality, drought stress may change the demographics of pathogens 9 ; pathogens subsequently drive forest mortality independently or in conjunction with drought-induced changes in the host’s physiological condition 11,12 . Pathogen infections also significantly alter physiological performance, such as inhibiting stomatal opening and the photosynthetic rate, thus triggering physiological changes similar to those triggered by drought stress 1315 . This, combined with the increased demand for energy and carbon for disease resistance, depletes the carbon reserve in the sink tissues 16 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that drought stress negatively affects photosynthetic gas exchange, however, some pathogens (da Silva et al, 2018) and their combination with drought ( Supplementary Table 4) have also been reported to have a similar impact. Ghanbary et al (2017) reported that drought and the pathogens O. persica and B. mediterranea significantly reduced stomatal conductance, photosynthetic rate, and maximum photochemical efficiency of photosystem II (Fv/Fm) in Q. brantii.…”
Section: Responses Of Forest Trees To Combined Biotic and Abiotic Strmentioning
confidence: 98%
“…Several individual biotic and abiotic stresses affect plant-water relations. For example, drought stress (McKiernan et al, 2017) and infection by fungal pathogens, which affect the vascular system (da Silva et al, 2018) influence the movement of water and reduce stem and leaf water potential. The simultaneous occurrence of these stresses may cause further reduction in water potential in plants.…”
Section: Responses Of Forest Trees To Combined Biotic and Abiotic Strmentioning
confidence: 99%
“…Conidia, aleuroconidia, and ascospores of Ceratocystis isolates from different hosts (e.g., eucalypts, cocoa, mango, teak, and atemoya) are capable of germinating, penetrating, and developing in the vessel elements of eucalypt plants within 6 h (Firmino et al 2015). The resistance of eucalypt plants to C. fimbriata is related to enzymatic activity (e.g., polyphenol oxidase and peroxidase activities) and accumulation of sugar, antimicrobial compounds (e.g., flavone, hesperetin, loganin, and nicotinamide), and phenolic compounds (Silva et al 2018;Pimenta et al 2017). Firmino et al (2018) concluded that the resistance of eucalypt to Ceratocystis wilt might be related to the capacity of plants to accumulate lignin in cells.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently no chemical molecules available for disease control. Deployment of resistant material is the only available and efficient method for controlling Ceratocystis wilt in eucalypt (Silva et al 2018;Alfenas et al 2009;Zauza et al 2004). Several eucalypt clones resistant to Ceratocystis wilt have been identified (Firmino et al 2013;Tumura et al 2012;Zauza et al 2004), but the mechanisms confering resistance to fungal infection have not yet been elucidated in detail.…”
Section: Introductionmentioning
confidence: 99%